The Effect of Incentive, Principal Leadership, and Motivation toward Teacher Professionalism in Conducting Learning Activity at Vocational High Schools - Lestari, Sri; Sumaryanto Florentinus, Totok; Made Sudana, I (Educational Management, 2019)
The aims of this study are to describe and analyze the influence of partial and simultaneous incentives. principal leadership. and motivation toward teacher professionalism in conducting learning activity. This study also examined the effect of incentives. principal leadership through motivation towards teacher professionalism in conducting learning activity. This study belongs to population research by using quantitative method and survey approach. Data collection used in this research was questionnaires which were distributed to 66 teachers. Data analysis that used in this research is multiple linear regression analysis and path analysis. The results showed that the effect of incentive on teacher motivation is 27.04%. Principal leadership affects teacher motivation as much as 17.89%. The effect of incentive and principal leadership on teacher motivation is 52.7%. Meanwhile. incentive does not have a significant effect on teacher professionalism because they only have an effect as much as 1.35%. The effect of principal leadership on teacher professionalism is 62.25%. Motivation does not have a significant effect on teacher professionalism. which is only 2.34%. There is a direct effect of incentive. principal leadership and motivation towards teacher professionalism which is equal to 54.7%. There is no effect of incentive on teacher professionalism through motivation because indirect effect is smaller than the value of direct effect. and also there is no indirect influence of leadership through motivation towards teacher professionalism in conducting learning activity.